2011
DOI: 10.1093/ejo/cjq182
|View full text |Cite
|
Sign up to set email alerts
|

Treatment times of Class II malocclusion: four premolar and non-extraction protocols

Abstract: The purpose of this study was to retrospectively compare the treatment times of Class II division 1 malocclusion subjects treated with four first premolar extractions or a non-extraction protocol and fixed edgewise appliances. Eighty-four patients were selected and divided into two groups. Group 1, treated with four first premolar extractions, consisted of 48 patients (27 males and 21 females) with a mean age of 13.03 years and group 2, treated without extractions, consisted of 36 patients (18 males and 18 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Many studies have reported that treatment duration was longer in extraction treatment, [6][7][8][9] but there were also studies that showed no difference. [10][11][12] Studies have shown that missed appointments, 8,13 bracket failure, 10,14 poor elastic wear, 8,10 and poor oral hygiene 8 can affect treatment duration.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that treatment duration was longer in extraction treatment, [6][7][8][9] but there were also studies that showed no difference. [10][11][12] Studies have shown that missed appointments, 8,13 bracket failure, 10,14 poor elastic wear, 8,10 and poor oral hygiene 8 can affect treatment duration.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 An infinite variety of appliances are available for the orthopedic correction of Class II malocclusion; these include both intraoral and extraoral appliances. 3,4,5,6 Among the intraoral orthopedic appliances,…”
Section: Introductionmentioning
confidence: 99%
“…2,5 Malocclusion treatment protocol also plays a role in determining treatment time in complete Class II malocclusion treatment. [2][3][4] It has been shown that treatment time is smaller, with better occlusal outcomes in complete Class II malocclusion treatment when performed with two-maxillary premolar extractions than when treated non-extraction or with four premolar extractions. [1][2][3] It has been speculated…”
Section: Intergroup Comparisonsmentioning
confidence: 99%
“…3 Treatment time in 4-premolar extraction and non-extraction protocols of complete Class II malocclusions are similar. 4 Consequently, it is speculated that the reason for the greater treatment success rate and efficiency, and the smaller treatment time in the 2-maxillary extraction protocol compared to the other two is because posterior teeth Class II anteroposterior discrepancy does not have to be corrected and consequently smaller patient compliance in using removable devices is necessary. [1][2][3]5,6 When Class I malocclusions treated with 4-premolar extractions were compared to complete Class II malocclusions, also treated with 4-premolar extractions, the results demonstrated better occlusal results and greater occlusal changes in the first group, corroborating this speculation.…”
Section: Introduction and Statement Of The Problemmentioning
confidence: 99%